Endoscopic vs. Microscopic Resection of Sellar Lesions—A Matched Analysis of Clinical and Socioeconomic Outcomes - Azad, Tej D.; Lee, Yu-Jin; Vail, Daniel; Veeravagu, Anand; Hwang, Peter H.; Ratliff, John K.; Li, Gordon (Frontiers in Surgery, 2017)
Background: Direct comparisons of microscopic and endoscopic resection of sellar lesions are scarce, with conflicting reports of cost and clinical outcome advantages. Objective: To determine if the proposed benefits of endoscopic resection are realized on a population-level. Methods: We performed a matched cohort study of 9,670 adult patients in the MarketScan database who underwent either endoscopic or microscopic surgery for sellar lesions. Coarsened matching was applied to estimate the effects of surgical approach on complication rates, length of stay (LOS), costs, and likelihood of postoperative radiation. Results: We found that LOS, readmission, and revision rates did not differ significantly between approaches. The overall complication rate was higher for endoscopy (47% compared to 39%, OR 1.37, 95% CI 1.22-1.53). Endoscopic approach was associated with greater risk of neurological complications (OR 1.32, 95% CI 1.11-1.55), diabetes insipidus (OR 1.65, 95% CI 1.37-2.00), and CSF rhinorrhea (OR 1.83, 95% CI 1.07-3.13) compared to the microscopic approach. Although the total index payment was higher for patients receiving endoscopic resection (32,959 compared to 29,977 for microscopic resection), there was no difference in long term payments. Endoscopic surgery was associated with decreased likelihood of receiving post-resection stereotactic radiosurgery (OR 0.67, 95% CI 0.49-0.90) and intensity-modulated radiation therapy (OR 0.78, 95% CI 0.65-0.93). Conclusion: Our results suggest that the transition from a microscopic to endoscopic approach to sellar lesions must be subject to careful evaluation. While there are evident advantages to transsphenoidal endoscopy, our analysis suggests that the benefits of the endoscopic approach have yet to materialize.